Exploring identity: A Critical Discourse Analysis on “Nepali Women in Politics Success and Challenges” - Gautam, Sushil; Chhetry, Tek Bahadur (Madhyabindu Journal, 2024)
The research paper explores the idea placed in the article “Nepali Women in Politics: Success and Challenges” by Bishnu Raj Upreti, Drishti Upreti and Yamuna Ghale published in the ‘Journal of International Women’s Studies’ on April 2020 from the perspectives of CDA, a relatively recent approach to analyzing discourse. The paper provides the definitions and overview of some CDA models mainly of Norman Fairclough, Ruth Wodak, T.A. Van Dijk and so on. Language, ideology and discourse are inseparable notions as we talk about media, translation and Critical Discourse Analysis (CDA). We get information from many sources which we use to interpret the world. Personal interactions with others provide us the insight with their knowledge and experience, cultural conventions and practices in their social world. On the other hand, television, radio, newspaper and magazines, the internet and many other sources with their different values provide us information. Language is the main mood through which most of the sources give information and most of these sources can be interpreted and analyzed using Critical Discourse Analysis (CDA). The paper will discuss how the discourse used by the three authors in the article shows women’s struggle for equality in Nepal for the establishment of their identity in the society by exposing themselves in politics.